2009
DOI: 10.1016/j.metabol.2008.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of apolipoprotein A5 in mice is not protective against body weight gain and aberrant glucose homeostasis

Abstract: Apolipoprotein A5 [APOA5] is expressed primarily in the liver and modulates plasma triglyceride levels in mice and humans. Mice overexpressing APOA5 exhibit reduced plasma triglyceride levels. Since there is a tight association between plasma triglyceride concentration and traits of the metabolic syndrome, we utilized transgenic mice overexpressing human APOA5 to test the concept that these mice would be protected from diet-induced obesity and insulin resistance. Male and female transgenic and wild-type mice o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 54 publications
1
12
0
Order By: Relevance
“…Shu et al ( 32 ) observed that both the hepatic TG content and the apoA-V lipid droplet association were increased in human apoA-V transgenic mice, whereas inactivation of the mouse apoA-V gene had little effect. Although the impact on plasma TG was not examined in that study, Pamir et al ( 45 ) found that when human apoA-V transgenic mice were fed a high-fat and high-sucrose diet, fasting plasma TG levels fell instead of increasing, suggesting that apoA-V gene expression had inhibited diet-induced hepatic VLDL-TG secretion. Werner et al ( 46 ) observed that hepatic steatosis induced by essential fatty acid defi ciency is accompanied by increased apoA-V gene expression; yet, Huang et al ( 47 ) found that plasma apoA-V levels were 45% lower in obese, insulin-resistant, dyslipidemic subjects, suggesting that hepatic steatosis, which is a concomitant condition of the metabolic syndrome, reduced hepatic apoA-V secretion.…”
Section: Discussionmentioning
confidence: 91%
“…Shu et al ( 32 ) observed that both the hepatic TG content and the apoA-V lipid droplet association were increased in human apoA-V transgenic mice, whereas inactivation of the mouse apoA-V gene had little effect. Although the impact on plasma TG was not examined in that study, Pamir et al ( 45 ) found that when human apoA-V transgenic mice were fed a high-fat and high-sucrose diet, fasting plasma TG levels fell instead of increasing, suggesting that apoA-V gene expression had inhibited diet-induced hepatic VLDL-TG secretion. Werner et al ( 46 ) observed that hepatic steatosis induced by essential fatty acid defi ciency is accompanied by increased apoA-V gene expression; yet, Huang et al ( 47 ) found that plasma apoA-V levels were 45% lower in obese, insulin-resistant, dyslipidemic subjects, suggesting that hepatic steatosis, which is a concomitant condition of the metabolic syndrome, reduced hepatic apoA-V secretion.…”
Section: Discussionmentioning
confidence: 91%
“…Mice were then randomly assigned to one of two groups for another 3 weeks of either continued ad libitum HFD feeding or to caloric restriction. For caloric restriction, mice were individually housed and given 60% of the HFD food consumption as monitored during weeks 10-12 as described ( 43 ). At the end of all feeding studies, mice were fasted for 4 h in the morning, bled from the retro-orbital sinus into tubes containing 1 mM to our knowledge.…”
Section: Methodsmentioning
confidence: 99%
“…WT mice fed the HFD have been repeatedly shown to gain body weight and fat, accompanied by systemic and adipose tissue infl ammation ( 11,14,15,43,46,51,58 ). What is not known is whether alterations in myeloidderived Abcg1 Ϫ / Ϫ worsen obesity or alter the course of body weight and fat loss during caloric restriction.…”
Section: Abcg1 Myeloid Defi Ciency Does Not Modulate Body Weight or Gmentioning
confidence: 99%
“…Whether increased levels of intracellular apoA-V affects LD formation, stability or residence time remains to be determined. However, the observation of Pamir et al [29] that APOA5 transgenic mice fed a diet high in fat and sucrose secrete lower amounts of TG is consistent with high apoA-V expression fostering cellular TG accumulation.…”
Section: Apoa-v As a Potential Regulator Of Tg Secretion Via Lipidmentioning
confidence: 97%